A randomized, controlled, crossover trial of oral midazolam and hydroxyzine for pediatric dental sedation (Pesquisa Odontológica Brasileira, 2003)
The effectiveness of oral midazolam in pediatric dentistry is controversial. This randomized, controlled, crossover, double blind clinical trial was conducted in order to study the effect of midazolam, used either alone or in association with hydroxyzine, during child dental treatment. Thirty seven dental sedation sessions were carried out on 11 ASA I uncooperative children less than five years-old. In each appointment children were randomly assigned to groups: P - placebo, M - midazolam (1.0 mg/kg), or MH - midazolam (0.75 mg/kg) plus hydroxyzine (2.0 mg/kg). Vital signs (blood pressure, breathing rate, pulse and oxygen saturation) and behavior parameters (consciousness, crying, movement, overall behavior) were evaluated every 15 minutes. Friedman and Wilcoxon statistical tests were used to compare groups and different moments in the same group. Normal values of vital signs were usually registered. Heart rate increased in groups P and M as the session went on. Group M presented less crying and movement at the first 15 minutes of treatment. Group MH caused more drowsiness at the beginning of the session. Overall behavior was better in group M than in groups P or MH. Group M produced effective sedation in 77% of the cases, and group MH did so in 30.8%. It was concluded that midazolam was effective and safe, and its association with hydroxyzine did not lead to additional advantages in pediatric dental sedation.